Indigenous student literacy outcomes in Australia: a systematic review of literacy programmes. Issue 1 (1st January 2021) - Gutierrez, Amanda; Lowe, Kevin; Guenther, John
ABSTRACT: Improving Indigenous students' literacy is a major priority area for the Australian Government, receiving significant funding to address below benchmark English literacy standardised test results. Despite this, recent benchmark tests suggest Indigenous students continue to achieve well below the national average. This systematic review discusses peer-reviewed and evidence-based publications that report on significant literacy programmes to investigate which aspects of literacy are their focus, which are identified as successful, conditions needed for success, barriers to success and measures of success. While most programs reported significant literacy improvements, all identified barriers to success and/or sustainability as outlined in this paper. This review also utilises the four resources literacy model and multiliteracies theories to map literacy gaps. When considering decades of literacy research, there were significant gaps in the represented literacy skills, with the dominant focus on codebreaking, and very few programs addressing critical literacies, multiliteracies or creativity skills. The review of the papers highlighted the need for consideration of ways to design balanced and place-based literacy programs; school-community literacy partnerships; access to training and resources for schools and communities around literacy and school/community research projects and agency for teacher and school leaders to be professional context-based decision-makers.